Small conductance calcium-activated potassium channel contributes to stress induced endothelial dysfunctions - Yang, Zhen; Li, Yingrui; Huang, Mengying; Li, Xin; Fan, Xuehui; Yan, Chen; Meng, Zenghui; Liao, Bin; Hamdani, Nazha; El-Battrawy, Ibrahim; Yang, Xiaoli; Zhou, Xiao-Bo; et al. (Microvascular research, 2024)
Patients with Takotsubo syndrome displayed endothelial dysfunction, but underlying mechanisms have not been fully clarified. This study aimed to explore molecular signalling responsible for catecholamine excess induced endothelial dysfunction. Human cardiac microvascular endothelial cells were challenged by epinephrine to mimic catecholamine excess. Patch clamp, FACS, ELISA, PCR, and immunostaining were employed for the study. Epinephrine (Epi) enhanced small conductance calcium-activated potassium channel current (ISK1-3) through activating α1 adrenoceptor. Phenylephrine enhanced edothelin-1 (ET-1) and reactive oxygen species (ROS) production, and the effects involved contribution of ISK1-3. H2O2 enhanced ISK1-3 and ET-1 production. Enhancing ISK1-3 caused a hyperpolarization, which increases ROS and ET-1 production. BAPTA partially reduced phenylephrine-induced enhancement of ET-1 and ROS, suggesting that α1 receptor activation can enhance ROS/ET-1 generation in both calcium-dependent and calcium-independent ways. The study demonstrates that high concentration catecholamine can activate SK1-3 channels through α1 receptor-ROS signalling and increase ET-1 production, facilitating vasoconstriction.
Online verfügbar: 18. Juni 2024, Artikelversion: 21. Juni 2024
Gesehen am 18.03.2025